Combating Noncommunicable Diseases in Kenya : An Investment Case - Mensah, Julia; Korir, Julius; Nugent, Rachel; Hutchinson, Brian (Washington, DC: World Bank, 2020)
Noncommunicable diseases such as cancer, diabetes, chronic lung diseases, and heart diseases are the leading cause of death and disability. In Kenya, the growing prevalence of these diseases is a major public health concern and a hindrance to long-term economic growth. This is because these conditions reduce human capital and divert societal resources. The high cost of managing the growing caseload of noncommunicable diseases (NCDs) also afflicts Kenyan families, businesses, and the government, and increasingly leads to impoverishment. Developing an appropriate policy response to the threat of NCDs requires a clear understanding of the economic impacts as well as the benefits of potential interventions, both from a health and an economic perspective. Such information allows policy makers to evaluate the trade-offs between different investment decisions, with the goal of ensuring that any interventions maximize the rewards to individuals and to society at large. Combating Noncommunicable Diseases in Kenya is one of a few published studies on the economic burden of NCDs in Kenya. It focuses on a limited set of conditions, aligned with the burden of NCDs in Kenya, and demonstrates both the long-term costs of these diseases and the strong health and economic benefits of scaling up interventions. It contributes to a growing body of analysis on NCDs in Kenya—and in Africa—and provides muchneeded evidence to facilitate advocacy and foster dialogue to confront this serious challenge.